2004
DOI: 10.1111/j.1538-7933.2003.00592.x
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of plasma concentrations of clotting factors and measures of a prethrombotic state in a protein C‐deficient family

Abstract: of plasma concentrations of clotting factors and measures of a prethrombotic state in a protein C-de®cient family. J Thromb Haemost 2004; 2: 242±7.Summary. Background: Earlier studies found strong support for a genetic basis for regulation of coagulation factor levels and measures of a prethrombotic state (D-dimer, prothrombin fragment 1.2). Objectives: Estimation of how much of the variation in the levels of coagulation factors and measures of a prethrombotic state, including measures of protein C activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 43 publications
4
64
0
Order By: Relevance
“…But VWF:Ag of these levels is known to be uncommonly associated with bleeding symptom and shows low heritability [27,28]. ations [5].…”
Section: Adamts13 (%)mentioning
confidence: 99%
“…But VWF:Ag of these levels is known to be uncommonly associated with bleeding symptom and shows low heritability [27,28]. ations [5].…”
Section: Adamts13 (%)mentioning
confidence: 99%
“…Levels of plasma VWF have been shown to be largely determined by genetic factors, with estimates of heritability in humans ranging from 25% to 32% by pedigree analysis, 7,8 to 66% to 75% in twin studies. 9,10 ABO blood group is responsible for one-third of the genetic variability in VWF plasma levels.…”
Section: Introductionmentioning
confidence: 99%
“…1 All the genes encoding hemostatic factors are potential candidates for thrombosis and studies in families and twins have demonstrated significant contributions of additive genetic factors to variance in these intermediate phenotypes. [2][3][4][5][6][7][8][9] Significant genetic correlations between hemostatic factors and thrombosis were identified in the GAIT study, indicating shared genes regulate plasma levels of hemostatic factors and susceptibility to thrombosis. 1 Although genetic factors contribute to variance in hemostatic factors, associations between common genetic variants of the genes encoding a variety of hemostatic components and CVD have generally been inconsistent.…”
mentioning
confidence: 99%